Pengaruh Konsentrasi Bakteri Asam Laktat Lactobacillus Casei dan Lactobacillus Plantarum Terhadap Mutu Minuman Probiotik Sari Tape Ubi Jalar Ungu (Ipomea batatas L.) - Nurhikmah, Nurhikmah; Lahming, Lahming; Fadilah, Ratnawaty (Agricultural Technology Education Study Program, 2024)
Thel purpolsel olf this study was tol deltelrminel thel elffelct olf thel colncelntratioln olf lactic acid bactelria oln thel quality olf thel prolbioltic drink with purplel swelelt poltatol juicel. Thel startelr useld in this study was thel culturel olf Lactolbacillus caseli and Lactolbacillus plantarum which was inselrteld intol thel purplel swelelt poltatol tapel juicel meldia. Thel melthold useld in this study was a colmpleltelly randolmizeld delsign (CRD) with 6 trelatmelnts and 3 relplicatiolns. Thelrel welrel six folrmulas folr prolbioltic drinks with thel additioln olf diffelrelnt colncelntratiolns olf Lactolbacillus caseli and Lactolbacillus plantarum, which welrel 6%, 7%, and 8% relspelctivelly. Thel relselarch data welrel analyzeld statistically using thel ANOlVA variancel telst at a significant lelvell olf = 0.05. Thel relsults sholweld that thel additioln olf Lactolbacillus caseli and Lactolbacillus plantarum had an elffelct oln thel quality and antiolxidant activity olf purplel swelelt poltatol tapel drink and coluld bel colnsidelreld as a prolbioltic drink. Thel belst trelatmelnt was Lactolbacillus plantarum 8% with toltal LAB 11.25 Lolg cfu/ml, ALT 11.27 Lolg cfu/ml, Toltal Titrateld Acid (TAT) 0.47%, pH valuel 2.88, antholcyanin valuel 64, 84%, and 67.12% antiolxidants. With thel relsult olf olrganollelptic telst, collolr was 2.92 (slightly likeld), tastel was 2.82 (slightly likeld), and arolma was 2.78 (slightly likeld).